2015
DOI: 10.1016/j.ajhg.2015.10.012
|View full text |Cite
|
Sign up to set email alerts
|

RTTN Mutations Cause Primary Microcephaly and Primordial Dwarfism in Humans

Abstract: Primary microcephaly is a developmental brain anomaly that results from defective proliferation of neuroprogenitors in the germinal periventricular zone. More than a dozen genes are known to be mutated in autosomal-recessive primary microcephaly in isolation or in association with a more generalized growth deficiency (microcephalic primordial dwarfism), but the genetic heterogeneity is probably more extensive. In a research protocol involving autozygome mapping and exome sequencing, we recruited a multiplex co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
52
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(59 citation statements)
references
References 28 publications
5
52
1
1
Order By: Relevance
“…Exome sequencing revealed two missense variants (compound heterozygous) of uncertain significance in the RTTN gene. Pathogenic variants in the RTTN gene have been reported in children with microcephaly, brain abnormalities, and primordial dwarfism, a phenotype that overlapped with ultrasound findings in our case …”
Section: Resultssupporting
confidence: 79%
“…Exome sequencing revealed two missense variants (compound heterozygous) of uncertain significance in the RTTN gene. Pathogenic variants in the RTTN gene have been reported in children with microcephaly, brain abnormalities, and primordial dwarfism, a phenotype that overlapped with ultrasound findings in our case …”
Section: Resultssupporting
confidence: 79%
“…The most severe outcomes of PMG occur in children with severe microcephaly (-3 SD or smaller). Patients with severe congenital microcephaly and PMG have for example, shown mutations in WDR62 (WD repeat-containing protein 62), NDE1, RTNN and RAB3GAP1/2 and RAB18 [240][241][242]. PMG with microcephaly or normal brain size, corpus callosum dysgenesis and cerebellar hypoplasia may also be related to tubulin and MT-motor gene mutations such as KIF1B binding protein, TUBA1A, TUBB, TUBB2B, TUBB3, and DYNC1H1 (see Tables 1 and 2) [156,199,237].…”
Section: 25a Polymicrogyria (Pmg)mentioning
confidence: 99%
“…We have previously shown that research-grade whole exome sequencing can uncover causal mutations that are missed by clinical exome sequencing (Ben-Omran et al 2015; Shaheen et al 2015; Shamseldin et al 2015). Therefore, we enrolled this patient in a research protocol that entails combined autozygome/exome analysis.…”
Section: Resultsmentioning
confidence: 99%